Leadership and Motivation form Nurses Performance through Work Loyalty - Maria Magdalena Sri Widiastuti; Mokhamad Natsir; Sina Setiyadi (Trescode Green Organization, 2024)
Efforts to improve performance are carried out with leadership that can perform its functions well, increasing employee work motivation and loyalty. This research analyzes the influence of leadership and work motivation on employee performance through work loyalty. They used the path analysis method, taking samples from 145 respondents and using simple random sampling on nurses at Panti Waluya Sawahan Hospital, Malang. The research results state that leadership and work motivation significantly affect employee performance. Leadership and work motivation have a significant effect on work loyalty. Work loyalty has a significant effect on employee performance. Leadership and work motivation influence employee performance through work loyalty at Panti Waluya Sawahan Hospital, Malang.